A1_3 Modelling the Sustain of an Electric Guitar - Davis, Yasmin; Drewes, Nora; Lomax, Thomas; Norman, Sarah (Physics Special Topics, 2020)
In this paper we aim to construct a model of the string vibrations and their sustain in solid body electric guitars, considering a driven body oscillation that drains energy from the string and decreases the sustain. We will apply this model to notes close (high E) and further away (low E) from the natural frequency of the body. For the high E, we find a sustain reduced by a factor of two to 1.1s due to the body, while the low E is essentially unaffected at 7.8s.